Pengolahan Limbah Ikan Menjadi Biodiesel dengan Radiasi Mikrogelombang - Purwaningrum, Shintawati Dyah; Sukaryo, Sukaryo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
The fish waste contains a lot of oil, so there needs to be a way to treat fish waste to be more useful. One way that can be done is to process it into biodiesel. Biodiesel production begins with taking oil from fish waste by steaming, fish waste oil was analyzed for free fatty acid levels, and obtained by 1.8%. The process was continued with esterification because the FFA value was above 1%, with a reaction time of 15 minutes and a 450watt microwave power. The esterification and transesterification process were carried out in a modified microwave. This study uses a variable change in the form of micro-wave (microwave) power variations of 300, 450, 600 and 800 watts and the ratio of moles of oil to methanol 1: 6, 1:12, 1:18, 1:24. The highest yield obtained by Biodiesel in reactant ratio 1:18 variable and 600 watt microwave power by 97%, while the lowest yield in variable 1: 6 with 300 watt microwave wave power by 88%. Biodiesel from fish waste produced was analyzed using GC-MS to determine the formation of methyl esters. The methyl esters contained in the form of stearic acid with an area of 21%. Analysis of the characteristics of biodiesel density was 863 kg/m3, viscosity was 3.12 mm2/s, cetane number was 55.72. From several characteristics test of biodiesel, fish waste is included in the biodiesel requirements of the Indonesian National Standard. Testing the water content is still high above the limit set by SNI biodiesel which is equal to 0.80%.